Closure of oroantral fistula by using buccal fat pad and buccal flap: a case report: Penutupan oroantral fistula menggunakan buccal fat pad dan flap bukal: laporan kasus - Arwiny Wulandari Hipi; Andi Tajrin; Muhammad Ruslin (Makassar Dental Journal, 2019)
Background: Oroantral fistula (OAF) is a pathological communication between the oral cavity and maxillary sinus which has its origin by multifactorial. The primary reason is the anatomic proximity of the root apices to the sinus floor or projection of the roots within the maxillary sinus. Aim: Describing a case about diagnosis and management of OAF by using buccal fat pad and buccal flap.Case: A 28-years-old male patient came to Dental Hospital of Hasanuddin University was diagnosed as OAF due to upper right molar tooth extraction with odontogenic chronic maxillary sinusitis and have been performed closing the fistula by using buccal fat pad and buccal flap. Conclusion: Patient with OAF and odontogenic chronic maxillary sinusitis have been treated by using buccal fat pad and buccal flap.